2022-VA-1642-ESGO Tricks to improve the laparoscopic extraperitoneal space in para-aortic lymphadenectomy. (20th October 2022) - Carbonell Lopez, Maria; Gracia, Myriam; Garcia, Virginia; Siegrist, Jaime; Rodriguez Gonzalez, Elena; Alonso, Maria; Dolores Diestro, Maria; Hernandez, Alicia; Zapardiel, Ignacio
Abstract : Introduction/Background: Minimal invasive surgery in gynecological cancer offers benefits over laparotomy in terms of fewer operative complications. There are two approaches to para-aortic lymphadenectomy: transperitoneal and extraperitoneal. The transperitoneal approach offers a greater working space and familiar landmarks, but sometimes requires bowel mobilization. The advantages of the extraperitoneal approach include operative feasibility in spite of previous abdominal surgery, decreased risk of direct bowel injury, and bowel adhesion formation. The disadvantages are a small working space, limited landmarks, and the risk of becoming disoriented. The use of some techniques to increase the surgical field may be helpful by making surgery easier and faster Methodology: We present a video with four surgical techniques to improve the viewing area in extraperitoneal para-aortic lymphadenectomy. Results: Accessory trocar for instrument insertion to raise the upper peritoneum in the form of a tent.- Placement of a clamp on the umbilical trocar placed in the peritoneal cavity to facilitate the outflow of CO2 to allow further distension of the retroperitoneal area.- Pneumatic balloon or Foley catheter can be placed to prevent the escape of CO2 into the intraperitoneal space in case of accidental opening of the peritoneum during entry into the retroperitoneal field.- For advanced surgeons, node dissection can be performed with an advanced sealing instrument with one hand while the other hand is used to lift the upper peritoneum in a tent to increase the working space. Conclusion: Laparoscopic para-aortic lymphadenectomy is a procedure with technical difficulties. The most important and basic requirements for appropriate lymphadenectomy are a correct surgical field development and a precise knowledge of anatomy to prevent accidental injuries. The use of some tricks can help to improve the surgical field to facilitate the surgical procedure.